Metabolic engineering of Escherichia coli for biosynthesis of β‐nicotinamide mononucleotide from nicotinamide - Yang Liu (Wiley, 2021)
Summary The β‐nicotinamide mononucleotide (NMN) is a key intermediate of an essential coenzyme for cellular redox reactions, NAD. Administration of NMN is reported to improve various symptoms, such as diabetes and age‐related physiological decline. Thus, NMN is attracting much attention as a promising nutraceutical. Here, we engineered an Escherichia coli strain to produce NMN from cheap substrate nicotinamide (NAM) and glucose. The supply of in vivo precursor phosphoribosyl pyrophosphate (PRPP) and ATP was enhanced by strengthening the metabolic flux from glucose. A nicotinamide phosphoribosyltransferase with high activity was newly screened, which is the key enzyme for converting NAM to NMN with PRPP as cofactor. Notably, the E. coli endogenous protein YgcS, which function is primarily in the uptake of sugars, was firstly proven to be beneficial for NMN production in this study. Fine‐tuning regulation of ygcS gene expression in the engineered E. coli strain increased NMN production. Combined with process optimization of whole‐cell biocatalysts reaction, a final NMN titre of 496.2 mg l‐1 was obtained.